Christian Themes and Motifs of Muslim Poets in Croatian Literature from Modern Times to the Present Day - Lončarević, Vladimir (Anafora, 2025)
In observing the development of Croatian literature from a religious and confessional point of view, one can recognize three sets of Christian intentions and tendencies: the Catholic, as substantial and supportive, the Protestant, and the Orthodox. In addition to them, Muslim or Islamic literature is also relevant. This paper aims to research the contact between Islamic and Christian faiths and cultures based on the poetry by Muslim poets in Croatian literature. After determining its scientific relevance and defining the methodological-hermeneutic approach to research, this topic was considered from the poets’ standpoint, by exploring their poetry collections, as well as relevant periodicals. The research included seventeen poets, all of whom are, with one exception, late writers. Works cited included only the works of Muslim writers. Based on examples, the research revealed the specifics of the poets’ use of Christian names and concepts as themes or motives in their respective poetries and some common features, mainly the Muslim poets’ familiarity with the Christian faith (names, terminology, doctrine, tradition, etc.) and the predominance of their affirmative use, whether the Islamic worldview is noticeable or not. In summary, it was concluded that Muslim poets in Croatian literature reach for Christian themes and motifs as accessible and familiar content. At the same time, they retain the religious and cultural contents and traditions from the Islamic spiritual circle, which sometimes results in the intertwining of Islamic views and Christian content. Granted, this is only an introduction to the subject, which, naturally, requires further research.